Constructing better roads with asphalt rubber - Pais, Jorge C. (2015)
Brazilians mixtures containing asphalt rubber were evaluated by mechanical laboratory tests. A conventional mixture with asphalt CAP-50/70 was produced as a mixture control. With the aim of compare the Brazilians mixtures performance, a Portuguese asphalt rubber mixture was tested as well. The testing set involved the determination of the mechanical properties, fatigue and permanent deformation, of asphalt rubber produced by wet process through two different systems: continuous blend and terminal blend. The asphalt rubber morphology was evaluated in order to determine the compatibility of the systems. The asphalt rubber mixtures exhibit good resistance to permanent deformation and prolonged fatigue life in relation to mixture control. Therefore it is concluded that the application of asphalt rubber alters the characteristics of asphalt mixture in a very beneficial way.